Pandemic disruptive factors in estate agency performance / Nurul Nabihah Zainal Abidin, Noraliza Basrah and Norbaya Ab Rahim - Zainal Abidin, Nurul Nabihah; Basrah, Noraliza; Ab Rahim, Norbaya (College of Built Environment, 2023)
The spread of COVID-19 that has affected on human health, it also affected on country's economy, world's population and distrupted the global way of life.